PENGARUH KUALITAS JASA TERHADAP KEPUASAN PASIEN JAMKESDA RAWAT INAP DI RSP DR.M.GOENAWAN PARTOWIDIGDO CISARUA BOGOR - Tintin Agustini; Titiek Tjahja Andari; Rachmat Gunawan (Fakultas Ekonomi Universitas Djuanda, 2015)
This study aims to determine the response inpatients jamkesda card holder on the quality of services on the RSP DR. M. Gunawan Partodigdo Cisarua Bogor, either simultaneously or partially. Forms of verification research, test instruments used. The testing was conducted on the validity and reliability test. Reliability testing is used to measure the consistency of responses. Test of validity is performed to determine whether all the questions (instrument) study to measure the research variables are valid. Criteria testing is done with a Cronbach Alpha sampling method using Non-Profitability sampling (random sampling), while the technique is simple random sampling. The samples used were 100 respondents. Data were analyzed using multiple linear regressions. The results showed the average responses of respondents in tangible dimension of service quality (enough); empathy (well, seriously); reliability (good); responsiveness (enough) and assurance (good). Average responses of respondents on patient satisfaction JAMKESDA card holder (satisfied). Based on the results of multiple linear regression analysis of the F test that simultaneously affect the service quality patient satisfaction jamkesda participants, T-test results showed that the tangible (X1) and reliability (X3) has a significant effect on the level of patient satisfaction JAMKESDA cardholders at home pain, whereas empathy (X2), responsiveness (X4) and assurance (X5) there is no significant effect on the level of patient satisfaction JAMKESDA on the RSP card holder DR.M. Gunawan Partowidigdo Cisarua Bogor..Keywords : Tangible , Empathy , Reliability , Responsiveness , Assurance , patient satisfaction JAMKESDA